The effect of nutrition education given to adolescent soccer players on nutritional status and knowledge level: experimental study - İSLAMOĞLU, AYŞE HÜMEYRA (My University, 2022)
Amaç: Bu çalışmada adölesan futbolcuların; temel beslenme, sıvı elektrolit alımı, kamp, antrenman ve müsabaka dönemi beslenme eğitimleri öncesi ve sonrasında beslenme bilgi düzeyleri ve besin tüketim durumlarındaki değişimleri saptamak amaçlanmaktadır. Gereç ve Yöntemler: Çalışmamıza toplamda 17 adölesan erkek futbolcu katılmıştır. Katılımcıların ortalama yaşı 18,17, boyu 179,52 cm, ağırlığı 71,7 kg, vücut yağ yüzdesi 10,34’tür ve futbol oynama süreleri 4-7 yıl arasındadır. Bu araştırma ön-son test içeren deneysel bir araştırmadır. Sporculara beslenme bilgi düzeyi ve besin tüketim durumunu iyileştirmek amacıyla 4 haftalık bir beslenme eğitim modülü uygulanmıştır. Elde edilen veriler IBM SPSS (Statistical Package for the Social Sciences) Statistics 21.0 programında istatistiksel olarak değerlendirilmiştir. Analizler sonucunda anlamlılık düzeyi p değeri<0,05 olarak kabul edilmiştir. Ön test ve son test karşılaştırmalı analizi Related-Samples Wilcoxon Signed Rank Test kullanılarak yapılmıştır. Bulgular: 4 haftalık eğitim sonrası sporcuların verilen tüm eğitim konularında beslenme bilgi düzeyleri artmıştır(p<0,05). Bununla birlikte besin tüketim sıklığı formu ile besin tercihlerinde iyileşmeler olduğu görülmüştür. En önemli değişim ekmek çeşidi tercihlerinde olmuştur. Her gün beyaz ekmek tüketimi oranı beslenme eğitimi öncesi %52,9’den %23,5’e düşmüştür. Her gün Kepek/Çavdar/Buğday Ekmeği tüketimi beslenme eğitimi öncesi %23,5 iken bu oran ise %70,6’ya yükselmiştir. Ayrıca 4 haftalık beslenme eğitimi sonrasında, su tüketim durumu değişimi istatistiksel olarak anlamlı artış göstermiştir. Bununla birlikte sporcuların, diyetisyenden destek alma durumlarında artış gözlenmiştir. Sonuç: Beslenme bilgi düzeyi ve besin tüketim durumları daha önce beslenme eğitimi almayan sporcularda düşüktür. Özellikle büyüme gelişmenin en önemli dönemlerden biri olan adölesan çağda sporculara verilen beslenme eğitim programları, sporcuların beslenme durumunu iyileştirir ve bilgi düzeylerini artırır

Objective: In this study, it is aimed to determine the changes in nutrition information levels and nutrient consumption status of adolescent soccer players before and after basic nutrition, liquid electrolyte intake, camp, training and competition nutrition trainings. Material and Methods: A total of 17 adolescent male soccer players participated in our study. The average age of the participants was 18.17, height was 179.52 cm, weight was 71.7 kg, body fat percent was 10.34 and the duration of playing football was between 4-7 years. This research is an experimental study that includes a preliminary test and a final test. A 4-week nutrition education module and a 45-question questionnaire were administered to the athletes before and after the training in order to improve their nutritional knowledge level and nutrient consumption status. The data obtained were statistically evaluated in the IBM-SPSS Statistics 21.0 program. As a result of the analyses, the significance level was accepted as p-value<0.05. The comparative analysis of the pre-test and the post-test was performed using the related-samples Wilcoxon signed rank test. Results: After 4 weeks of training, the nutritional knowledge levels of the athletes increased in all training subjects (p<0.05). However, it was observed that there were improvements in food consumption frequency form and food preferences. The most important change was in the choice of bread type. The rate of consumption of white bread every day decreased from 52.9% to 23.5% before the nutrition education. While the consumption of Bran/Rye/Wheat Bread every day was 23.5% before the nutrition education, this rate increased to 70.6%. In addition, after 4 weeks of nutrition education, the change in water consumption status showed a statistically significant increase. However, an increase has been observed in the cases of athletes receiving support from a dietitian. Conclusion: Nutritional knowledge level and food consumption status are low in athletes who don’t receive support from a dietitian. Nutrition education programs given to athletes in adolescence, which is one of the most important periods of growth and development, improve the nutritional status of athletes and increase their knowledge level
Adölesan futbolcularda beslenme eğitiminin, beslenme durumu ve bilgi düzeyine olan etkisi: deneysel çalışma
Keywords: Futbol; adölesan; beslenme; eğitim; Soccer; adolescent; nutrition; education